The cost-effectiveness of radon-induced lung cancer prevention in schools - Kennedy, C; Gray, A (2000)
An economic evaluation of a radon-induced lung cancer prevention programme for schools in the United Kingdom is undertaken in this study, which presents a cost-effectiveness analysis with a generalisable model for estimating the cost-effectiveness of a radon remediation programme for schools from a societal perspective. It follows the guidelines for the methodological framework now considered appropriate in the economic evaluation of health interventions and employs best available national UK data and information from Northamptonshire on the costs and effectiveness of radon identification and remediation in schools, and the costs and health impact of lung cancer cases for all state schools in Northamptonshire between 1993 and 1997 (348 schools, including 170 adult staff and 1820 pupils). The resultant cost-effectiveness ratio was £7550 per life-year gained in 1997 UK pound sterling. Results from the sensitivity analysis show that the ratio is particularly sensitive to assumptions concerning two parameters: the average capital cost of remediation and discount rate applied to life years. This study highlights the need for the evaluation of other schools remediation-based radon-induced lung cancer prevention programmes in other countries using similar methodological techniques. Compared to other health interventions in the UK, the schools programme has a favourable ratio. When compared to other lung cancer prevention programmes available, however, the schools programme ratio is less favourable. Uncertainties remain around increased risks from childhood exposure to indoor radon.